Comparative Performance Analysis of RabbitMQ and Kafka Message Queue Systems in Spring Boot and ASP.NET Environments - Kamiński, Filip; Kłonica, Radosław; Pańczyk, Beata (Journal of Computer Sciences Institute, 2025)
The article analyzes and compares the performance of Kafka 4.0 and RabbitMQ 4.1 in applications built with Spring (Kotlin) and .NET. Given the growing importance of microservices and event-driven architectures, the research examines message throughput, resource consumption, and stability under different loads. Two applications were developed to measure performance in terms of processing speed, CPU, and memory usage. The study also explores architectural considerations and factors affecting performance. The findings offer insights into when each system is most suitable, helping developers make informed decisions based on project requirements. The results show that Kafka performs better in .NET environments with up to 38% higher throughput and 40% lower latency while RabbitMQ is more efficient in Spring Boot setups, using nearly 29% less memory and delivering responses 25% faster.